1990
DOI: 10.1111/j.1440-1681.1990.tb01357.x
|View full text |Cite
|
Sign up to set email alerts
|

Renal and Myocardial Adrenoceptors in Steroid Contraceptive‐induced Hypertension in Rats

Abstract: 1. Systolic blood pressure (SBP), bodyweight, organ weight, renal P-adrenoceptor and myocardial P-and myocardial al-adrenoceptor characteristics were investigated in female Sprague-Dawley rats after chronic subcutaneous (s.c.) administration of ethynyloestradiol (EE2, 0.2 pg/day), levonorgestrel (NG, 2.0 pg/day) separately and in combination (EE2/ NG).2. EE2 caused a sustained increase in SBP from 6 weeks (maximum at 14 weeks, 4-22 mmHg compared to control) which was accompanied by increased kidney and ventric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Many previous studies (3,17,19,24,42,49) showed that contraceptives or estrogen treatment induce hypertension in humans and animals. However, the mechanisms on the pressor effect of estrogen are still inconsistent with each other.…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies (3,17,19,24,42,49) showed that contraceptives or estrogen treatment induce hypertension in humans and animals. However, the mechanisms on the pressor effect of estrogen are still inconsistent with each other.…”
Section: Discussionmentioning
confidence: 99%
“…Ethinyl Estradiol (30μg/day; Fisher Scientific) and Levonorgestrel (30μg/day; Fisher Scientific), a progestin, were dissolved in 0.01ml of sesame oil and delivered subcutaneously at the nape of the neck daily for 8days, the approximate duration of two estrous cycles, during mid to late adolescence (p50–p58), with control animals receiving vehicle. Although, a wide range of rodent doses of EE2 and Levonorgestrel have been reported ( Santoru et al, 2014 ; Prakapenka et al, 2018 ; Olaniyi and Olatunji, 2019 ), the doses chosen here aimed to match those used consistently for suppressing ovulation and mimicking effects observed in humans, such as increased blood pressure ( Geraghty et al, 1990 ), and for comparability to existing rodent literature on subcutaneous delivery of Levonorgestrel and EE2 ( Follesa et al, 2002 ; Simone et al, 2015 ). Many doses for orally delivered EE2 and Levonorgestrel in rats also fall in this range ( Nowaczyk-Dura and Czekaj, 1998 ; Guerra et al, 2002 ; Olatunji et al, 2017 ; Olaniyi and Olatunji, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Ethinyl Estradiol (EE2, 30µg/day) and Levonorgestrel (30 µg/day), a progestin, were dissolved in in 0.01 mL of sesame oil and delivered subcutaneously at the nape of the neck daily for the duration of two estrous cycles during mid to late adolescence (p50 to p58). Although a wide range of rodent doses of EE2 and Levonorgestrel have been reported(114116), the doses chosen here aimed to match those used consistently for suppressing ovulation and mimicking effects observed in humans, such as increased blood pressure(117), and for comparability to existing rodent literature on subcutaneous delivery of Levonorgestrel and EE2(118120). Many doses for orally delivered EE2 and Levonorgestrel in rats also fall in this range(82,115,121,122).…”
Section: Methodsmentioning
confidence: 99%